2016
DOI: 10.1007/s40519-016-0253-0
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic medications in adult and adolescent eating disorders: clinical practice versus evidence-based recommendations

Abstract: Treatment recommendations suggest medication should not be the primary treatment for EDs and empirical evidence demonstrates their ineffectiveness in AN. Nevertheless, there were no differences in frequency found between diagnostic groups, confirming little relationship between evidence-based recommendations and actual clinical use for those referred to a specialized ED treatment facility. This study adds new evidence regarding age-based comparisons of psychotropic prescription frequency in clinical EDs and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…Broadly, most published literature based on randomized controlled trials has concluded that SSRIs offer no more benefit than placebo, yet they are used very frequently (Fazeli et al, 2012;Garner et al, 2016). Research has demonstrated clear links between AN and serotonergic activity (e.g., Bailer et al, 2013), but it is yet unclear how, when, or for whom SSRI medication is most effective.…”
Section: Approximately 4 Months Later Patient A's Mother Reported Thatmentioning
confidence: 99%
See 1 more Smart Citation
“…Broadly, most published literature based on randomized controlled trials has concluded that SSRIs offer no more benefit than placebo, yet they are used very frequently (Fazeli et al, 2012;Garner et al, 2016). Research has demonstrated clear links between AN and serotonergic activity (e.g., Bailer et al, 2013), but it is yet unclear how, when, or for whom SSRI medication is most effective.…”
Section: Approximately 4 Months Later Patient A's Mother Reported Thatmentioning
confidence: 99%
“…Despite these evidence-based recommendations, one study found that 78.7% of adolescents in a residential adolescent treatment program and 89.6% of adults in an adult partial hospitalization program were prescribed psychotropic medications, most frequently antidepressants (Garner, Anderson, Keiper, Whynott, & Parker, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…19 - 21 Bupropion is contraindicated due to increased risk of seizures in anorexic patients. 19 , 21 , 28 Garner et al 29 reported that antidepressants are widely prescribed to adults and adolescent anorexic patients despite recommendations in treatment guidelines. Antidepressants were commonly prescribed to 87.9% of studied individuals (n = 287, age = 23.2 ± 10.4 years, BMI = 16.5 ± 1.6) with 79% receiving a selective serotonin reuptake inhibitor (SSRI).…”
Section: Introductionmentioning
confidence: 99%
“…Antidepressants were commonly prescribed to 87.9% of studied individuals (n = 287, age = 23.2 ± 10.4 years, BMI = 16.5 ± 1.6) with 79% receiving a selective serotonin reuptake inhibitor (SSRI). 29 This article discusses the safety of different antidepressants in AN and summarizes recent evidence and highlights potential benefits of use of select SSRIs and mirtazapine in adult anorexic patients during acute and maintenance treatment phases.…”
Section: Introductionmentioning
confidence: 99%
“…There were 506 females (280 PHP and 226 RES) and 29 males (11 PHP and 18 RES). The majority of patients were admitted on at least one psychotropic medication [18]. The retrospective chart review was approved by the Clinic Institutional Review Board and it was determined to comply with the Health Insurance Portability and Accountability Act guidelines.…”
Section: Introductionmentioning
confidence: 99%